2000
DOI: 10.1104/pp.122.2.471
|View full text |Cite
|
Sign up to set email alerts
|

The Genepat-2, Which Induces Natural Parthenocarpy, Alters the Gibberellin Content in Unpollinated Tomato Ovaries

Abstract: We investigated the role of gibberellins (GAs) in the effect of pat-2, a recessive mutation that induces facultative parthenocarpic fruit development in tomato (Lycopersicon esculentum Mill.) using near-isogenic lines with two different genetic backgrounds. Unpollinated wild-type Madrigal (MA/wt) and Cuarenteno (CU/wt) ovaries degenerated, but GA 3 application induced parthenocarpic fruit growth. On the contrary, parthenocarpic growth of MA/pat-2 and CU/pat-2 fruits, which occurs in the absence of pollination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
123
3
26

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 31 publications
(40 reference statements)
16
123
3
26
Order By: Relevance
“…In contrast to the Chs RNAi tomato, parthenocarpic fruit development of all these pat mutants is independent of pollination. At least some of these mutants (pat2, pat3, and pat4) contain increased GA levels in their parthenocarpic fruits, suggesting that the ability of these mutants to develop parthenocarpic fruits is due to alterations in GA metabolism (Fos et al, 2000(Fos et al, , 2001. Clearly, fruit development is controlled by complex processes, including multiple plant growth hormones and cross talk between regulatory plant hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Chs RNAi tomato, parthenocarpic fruit development of all these pat mutants is independent of pollination. At least some of these mutants (pat2, pat3, and pat4) contain increased GA levels in their parthenocarpic fruits, suggesting that the ability of these mutants to develop parthenocarpic fruits is due to alterations in GA metabolism (Fos et al, 2000(Fos et al, , 2001. Clearly, fruit development is controlled by complex processes, including multiple plant growth hormones and cross talk between regulatory plant hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting parthenocarpic fruit growth is a clear demonstration of the importance of hormones in fruit initiation and development. There are a number of parthenocarpic tomato mutants, such as pat, pat2 and pat3/4, in which it was shown that the GA content and/or GA biosynthesis were increased signiWcantly (Mazzucato et al 1998;Fos et al 2000Fos et al , 2001Olimpieri et al 2007). Furthermore, overexpression of the iaaM gene, which encodes an enzyme involved in auxin biosynthesis, also induced parthenocarpic fruit development in tomato and many other species (Rotino et al 1997;Mezzetti et al 2004).…”
mentioning
confidence: 99%
“…In tomato, the GA biosynthetic genes CPS, GA20ox, GA3ox, GA2ox and GA4 have been isolated (Rebers et al, 1999 andSerrani et al, 2007). The process of fruit set in tomato involves GA1 as the bioactive GA molecule and the early 13-hydroxylation pathway as the primary metabolic pathway (Serrani et al, 2007 andFos et al, 2000). Pollination mediates fruit set through GA biosynthesis, which is mainly achieved by the up-regulation of GA20ox (Serrani at al., 2007).…”
Section: Introductionmentioning
confidence: 99%